The 13042G→A/ND5 mutation in mtDNA is pathogenic and can be associated also with a prevalent ocular phenotype. Issue 7 (30th June 2006) - Valentino, M L; Barboni, P; Rengo, C; Achilli, A; Torroni, A; Lodi, R; Tonon, C; Barbiroli, B; Fortuna, F; Montagna, P; Baruzzi, A; Carelli, V
Abstract : Background: Overlapping phenotypes including LHON, MELAS, and Leigh syndrome have recently been associated with numerous mtDNA point mutations in the ND5 gene of complex I, now considered a mutational hot spot. Objective: To identify the mtDNA defect in a family with a prevalent ocular phenotype, including LHON-like optic neuropathy, retinopathy, and cataract, but characterised also by strokes, early deaths, and miscarriages on the maternal line. Results: Sequencing of the entire mitochondrial genome from the proband's muscle DNA identified the heteroplasmic 13042G→A transition, which was previously described only once in a patient with a different mitochondrial disease. This mutation fulfils the major pathogenic criteria, inducing an amino acid change (A236T) at an invariant position in a highly conserved domain of the ND5 gene. Phosphorus magnetic resonance spectroscopy in the proband disclosed an in vivo brain and skeletal muscle energy metabolism deficit. Conclusions: These findings conclusively establish the pathogenic role of the 13042G→A mutation and underscore its variable clinical expression.